1996
DOI: 10.5144/0256-4947.1996.381
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Impaired Glucose Tolerance in Saudi Arabia

Abstract: This study was undertaken to determine the prevalence of diabetes mellitus (DM), insulin-dependent diabetes mellitus (IDDM), noninsulin-dependent diabetes mellitus (NIDDM) and impaired glucose tolerance (IGT) in different areas of Saudi Arabia. A household survey was conducted in 34 different areas of Saudi Arabia. Demographic data and medical history were taken and filled. Fasting and two-hour "post-glucose load" blood samples were collected from 23,493 Saudi males and females and blood glucose was estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 5 publications
2
54
1
Order By: Relevance
“…Physiological maneuvers, such as calorie and salt restriction and regular physical exercise, are shown to improve tissue sensitivity to insulin and hence lower blood pressure both in normotensive and hypertensive diabetics. 16 In Saudi Arabia, the prevalence of DM is high, 6,7 and with the increase in prevalence of HT in diabetics, as shown in this study, the associated morbidity and complications are expected to increase. Hence, control of DM and HT by appropriate methods, particularly dietary restriction of calories and sodium, and regular physical exercise, must be stressed in order to decrease both the prevalence of HT and NIDDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological maneuvers, such as calorie and salt restriction and regular physical exercise, are shown to improve tissue sensitivity to insulin and hence lower blood pressure both in normotensive and hypertensive diabetics. 16 In Saudi Arabia, the prevalence of DM is high, 6,7 and with the increase in prevalence of HT in diabetics, as shown in this study, the associated morbidity and complications are expected to increase. Hence, control of DM and HT by appropriate methods, particularly dietary restriction of calories and sodium, and regular physical exercise, must be stressed in order to decrease both the prevalence of HT and NIDDM.…”
Section: Discussionmentioning
confidence: 99%
“…Our extensive studies during a national project on DM have shown a high prevalence of NIDDM, obesity, overweight and HT in the Saudis. [6][7][8][9]30 This study on a group of diabetic and nondiabetic Saudis has revealed that the prevalence of HT is significantly higher in the male and female diabetics in comparison to nondiabetics. In males, the prevalence of HT is increased almost 2.6 times in the diabetic group, while in the female diabetics, the prevalence of HT is increased almost 5.7 times.…”
Section: Discussionmentioning
confidence: 99%
“…The screening procedure and the results of these investigations have been published elsewhere. [14][15][16][17][18][19][20] The patients suffering from diabetes mellitus were diagnosed, based on the criteria published by the World Health Organization, [21][22] as follows: Fasting venous blood glucose ≥6.7 mmol/L (120 mg/dL) and/or two-hour post-glucose load ≥10.0 mmol/L (≥180 mg/dL) were considered diabetic. 21,22 Differential diagnosis between non-insulin-dependent diabetes mellitus (type II DM) and insulin-dependent diabetes mellitus (type I) was based on the age of onset and the mode of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…In Saudi Arabia, in particular, the prevalence of diabetes mellitus has increased dramatically (El-Hazmi and Warsy, 1989;El-Hazmi et al, 1998). Within the last 20 years the prevalence of diabetes mellitus in Saudi adults has increased by sixfold (Fatani et al, 1987;Al-Nozha et al, 2004).…”
Section: Introductionmentioning
confidence: 99%